PELAKSANAAN PRAKTEK MENGAJAR BAGI GURU PESERTA PENDIDIKAN JARAK JAUH YANG TINGGAL DI WILAYAH TERPENCIL - Kadarko, Wahyuni; Novita, Dian; Delfi, Refni (Jurnal Pendidikan, 2010)
This study aims to identify problems facing by participants in experiencing teaching pratice under The Strengthening Teaching Competency Programme. An evaluation method was employed through problem and issues maping, interpreting problem  dynamics, and improving actions. A qualitative-naturalistic approach with inteview was conducted during April-July 2009 to participants of Lower Secondary School Teacher Training  who live  in remote and rural areas in  Bandung, Bogor and Serang region. Interview was also   conducted to tutors, supervisors, programme manager, remote-school principals, peer teachers and students involved in the  teaching practicum/exercise. Observations and documentary study were employed to support the data of the interview. Problems  identified as  the low performance of  supervisory officials and partnership schools in guiding  student teachers in  developing didactic materials for both practicum and final exam. Most participants become stressed due to the absence of a definite timetable guidance process both in the process of lesson plan development, implementation of practicum and execution of final exams. It was suggested to redesign the current system with a more reliable system for participants coming from remote areas who wish to carry out teaching practice.